2009
DOI: 10.2174/138920209788920976
|View full text |Cite
|
Sign up to set email alerts
|

The Story of SPATA2 (Spermatogenesis-Associated Protein 2): From Sertoli Cells to Pancreatic Beta-Cells

Abstract: In an attempt to isolate new spermatogenesis-associated genes, pd1 was initially identified and cloned as a novel human cDNA sequence from testis cDNA library. The novel gene was submitted to GenBank under accession n° U28164 in 1996. PD1 expression was demonstrated at the Sertoli cell level with a production which appeared to be under the influence of neighbouring spermatogenic cells. The rat orthologue of human pd1 was further cloned and, according to the Gene Nomenclature Committee, was renamed spata2 (sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition to these female-related genes, our study observed significantly higher expression of TSSK4, spermatogenesis-associated protein 17 (SPAG17), SPAG8, sperm motility kinase X (SMKX) and SP17 in hermaphroditic gonads than in resting gonads, and the expression difference might be associated with the maintenance of spermatogenesis. The spermatogenesis-associated gene (SPATA), a testis-specific gene, played an important role in maintaining the physiological function of germ cells involved in the regulation of apoptosis during spermatogenesis [ 86 ]. SPATA4 has previously been confirmed to be specifically expressed in the testes of animals ranging from mammals to birds [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these female-related genes, our study observed significantly higher expression of TSSK4, spermatogenesis-associated protein 17 (SPAG17), SPAG8, sperm motility kinase X (SMKX) and SP17 in hermaphroditic gonads than in resting gonads, and the expression difference might be associated with the maintenance of spermatogenesis. The spermatogenesis-associated gene (SPATA), a testis-specific gene, played an important role in maintaining the physiological function of germ cells involved in the regulation of apoptosis during spermatogenesis [ 86 ]. SPATA4 has previously been confirmed to be specifically expressed in the testes of animals ranging from mammals to birds [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, it was shown that Atg3 is required for S. Typhimurium-mediated autophagy (Huett et al, 2009). The role of Spata2 is not very clear in the cell death; it is a coregulator of apoptosis and autophagy and the molecular mechanism of action of this gene is still under investigation (Maran et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The SPATA2L gene is a paralog of SPATA2, which is involved in spermatogenesis (Graziotto et al, 1999;Onisto et al, 2000). SPATA2L has been reported to have enriched expression in the brains of zebrafish (Danio rerio) (Moro et al, 2002;Maran et al, 2009), which makes it an interesting candidate for further analysis in the ruff, as the morphs show pronounced differences in testes volume index (Küpper et al, 2016) and relative testes size (Supplementary Figure 2). Our allelic imbalance results add to previous research that has shown allelic imbalance for another gene within the inversion, MC1R, where Satellites have reduced expression from the inversion allele in dark colored feathers, compared to Independents (Schwochow-Thalmann, 2018).…”
Section: Allelic Imbalance Across Tissues In Inversion Morphsmentioning
confidence: 99%